Persistent induction of goblet cell differentiation in the airways: Therapeutic approaches - Reid, A.T.; Veerati, P.C.; Gosens, R.; Bartlett, N.W.; Wark, P.A.; Grainge, C.L.; Stick, S.M.; Kicic, Anthony; Moheimani, F.; Hansbro, P.M.; Knight, D.A. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
© 2017 Dysregulated induction of goblet cell differentiation results in excessive production and retention of mucus and is a common feature of several chronic airways diseases. To date, therapeutic strategies to reduce mucus accumulation have focused primarily on altering the properties of the mucus itself, or have aimed to limit the production of mucus-stimulating cytokines. Here we review the current knowledge of key molecular pathways that are dysregulated during persistent goblet cell differentiation and highlights both pre-existing and novel therapeutic strategies to combat this pathology.